Teachers Awareness of Students’ Anxiety in Math Classroom: Teachers’ Treatment VS Students’ Anxiety - Wanda Nugroho Yanuarto (Journal of Education and Learning (EduLearn), 2016)
Math anxiety is a common phenomenon which can have a negative impact on numerical and arithmetic performance. However, so far little is known about the underlying neurocognitive mechanisms. This mini review provides an overview of studies investigating the neural correlates of math anxiety which provide several hints regarding its influence on math performance: while behavioral studies mostly observe an influence of math anxiety on difficult math tasks, neurophysiological studies show that processing efficiency is already affected in basic number processing. The purpose of this study is to provide some treatments to overcome students’ anxiety in math classroom at The University of Muhammadiyah Purwokerto, Indonesia especially in Math Department, but before it has attempted to investigate the factors that students’ anxiety can possibly stem from, both within the classroom environment and out of classroom in the wilder social context.